Pengecekan Gula Darah Dan Tekanan Darah Gratis Pada Lansia Di Puskesmas Tiban Baru - Delladari Mayefis; Suci Fitriani Sammulia; Aprilya Sri Racmayanti; Sri Hainil; Anjeli Firanka; Aulia Salwa (Universitas Muhammadiyah Manado, 2021)
The aging process in the elderly causes a decrease in glucose tolerance and basal metabolism, which affects blood sugar control. The activities and conditions of older adults influence their nutritional needs, which impact total calorie intake. Types of blood glucose level checks, including fasting, post-prandial, and others, are used to monitor elderly health conditions related to diabetes. Seniors are also susceptible to hypertension, which can cause serious complications such as stroke and heart disease. WHO notes the high prevalence of hypertension worldwide, emphasizing the importance of early detection and appropriate management to prevent adverse impacts on public health